Correlation between physiological and biochemical variables during short term adequate protein intake combined with resistance exercise in sedentary adults - Kyung-Wan Baek; Jong-Hwa Won; Chae-Been Kim; Jung-Jun Park (Scientific Reports)
Abstract This study aimed to clarify the pure synergistic effect of an adequate protein intake (1.5 g/kg body weight/day) and resistance exercise (RE) on muscle strength, body composition, and metabolic markers in sedentary adults, excluding confounders arising from excessive protein intake or impaired protein turnover. A double-blind randomized controlled trial was performed on apparently healthy sedentary adult participants (n = 34). RE was performed for 4 weeks in the placebo (PLA-EX, n = 17) and whey protein supplement groups (PRO-EX, n = 17). Body composition, isokinetic muscular function, resting metabolic rate, blood biochemical variables, and liver ultrasound findings were analyzed and compared before and after the intervention. Both the PLA-EX and PRO-EX groups experienced significantly reduced body weight (PLA-EX, p < 0.001; PRO-EX, p < 0.01), body mass index (PLA-EX, p < 0.01; PRO-EX, p < 0.01), and body fat percentage (PLA-EX, p < 0.01; PRO-EX, p < 0.0001) after the intervention. In addition, serum adiponectin (PLA-EX, p < 0.0001; PRO-EX, p < 0.001), leptin (PLA-EX, p < 0.05; PRO-EX, p < 0.0001), growth/differentiation factor 8 (PLA-EX, p < 0.05; PRO-EX, p < 0.01), albumin (PLA-EX, p < 0.05; PRO-EX, p < 0.01), total cholesterol (PLA-EX, p < 0.001; PRO-EX, p < 0.0001), triglycerides (PLA-EX, p < 0.0001; PRO-EX, p < 0.0001), and controlled attenuation parameters measured by liver ultrasound were significantly decreased (PLA-EX, p < 0.05; PRO-EX, p < 0.0001). The PRO-EX group showed no significant difference in circulating free fatty acid levels before and after the intervention, whereas PLA-EX levels decreased after the intervention (p < 0.01). Muscle mass (p < 0.05), muscle strength (p < 0.001), and insulin-like growth factor 1 (p < 0.05) were significantly increased by the intervention in the PRO-EX group but not in the PLA-EX group. Testosterone (p < 0.01), high-density lipoprotein cholesterol (p < 0.01), aspartate aminotransferase (p < 0.0001), and alanine aminotransferase (p < 0.001) were significantly reduced in the PRO-EX group but not in the PLA-EX group. The combination of RE and adequate protein intake (1.5 g/kg body weight/day) synergistically increased fat metabolism, induced an increase in IGF-1 in the blood, and increased muscle mass and strength in sedentary adults. Clinical Trial: The clinical trial described in this paper was registered at https://cris.nih.go.kr under the registration number KCT-0008696 (first trial registered 09/08/2023).